2021
DOI: 10.22454/fammed.2021.314886
|View full text |Cite
|
Sign up to set email alerts
|

Well-being in Residency: Impact of an Online Physician Well-being Course on Resiliency and Burnout in Incoming Residents

Abstract: Background and Objectives: Wellness in residency has come to the forefront of national graduate medical education initiatives. Exponential growth in knowledge and skill development occurs under immense pressures, with physical, mental, and emotional stressors putting residents at burnout risk. The Accreditation Council for Graduate Medical Education requires programs to attend to resident wellness, providing the structure, environment, and resources to address burnout. This study’s purpose was to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Understanding colleagues better and supporting each other (12) I was able to understand my colleagues better. I determined that my colleagues' grievances were similar to mine.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Understanding colleagues better and supporting each other (12) I was able to understand my colleagues better. I determined that my colleagues' grievances were similar to mine.…”
Section: Discussionmentioning
confidence: 97%
“…Among the North American residency programs, various institutional and experimental methods of resilience management have been studied. These include the Wellness Committee run by residents, [9] workshops to improve pediatric residents' emotional intelligence, [10] a mindfulness meditation program for family medicine residents, [11] an online wellbeing course for family medicine residents, [12] a wellness program for otolaryngology residents, [13] a mindfulness-based cognitive training program for surgical residents, [14] and an online resilience course for psychiatry residents. [15] These studies reported improvements in residents' exhaustion and stress levels, resilience, wellness scores, emotional intelligence, and mindful awareness.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to identify which interventions have the most impact in reducing resident burnout. There have been recent studies on a wide variety of interventions including resident retreats [27], on-line physician well-being courses [28], a humanistic mentorship program [29] and a mind-body skills group in psychiatric residency training [30]. A systemic review of skill-based programs used to reduce physician burnout in graduate medical education was published in 2021 [31].…”
Section: Discussionmentioning
confidence: 99%
“… 10 Surely, individual attributes like resilience and mindfulness are consistently linked to lower burnout and higher well-being in the education literature. 11 In what situation would these variables not correlate? The fact is that the learning environment (and not individual attributes) is known to be the primary driver of physician and trainee distress, 12 and IFWs have done little to nothing to improve this problem on a global scale.…”
Section: The Main Problems With Individual-focused Wellness Intervent...mentioning
confidence: 99%